Strategies for Addressing Poor Statistical Literacy Among Health Scientists and Science Communicators - Deonandan, Raywat (Université d'Ottawa | University of Ottawa, 2016)
Statistical literacy (SL) is an aspect of numeracy and a core educational competency. Overall levels of SL in North American society may be in decline, while evidence abounds of poor SL among researchers globally. Three strategies are recommended to help address poor SL among scholars and science communicators, with a particular focus on the health and medical sciences: (1) mandatory inclusion of computerized statistical platforms in undergraduate statistics classes; (2) requirement for statistical review in peer-reviewed paper submissions; and (3) the exploration of novel methods of results communication.
Keywords: education; statistics